2014
DOI: 10.1186/1746-1596-9-91
|View full text |Cite
|
Sign up to set email alerts
|

Insulin therapy and colorectal cancer risk among type 2 diabetes mellitus patients: a systemic review and meta-analysis

Abstract: BackgroundInsulin is widely used in patients with type 2 diabetes mellitus (T2DM). More attention was focused on its higher risk of colorectal cancer (CRC). This meta-analysis examined the relationship between levels of insulin use and the risk of CRC.MethodsA meta-analysis using data from 12 published epidemiologic studies (7 case–control, and 5 cohort studies) published before Jan. 2014 was done to examine the association between insulin use and CRC. Random effects analyses were done to calculate relative ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
(24 reference statements)
0
32
0
Order By: Relevance
“…Unfortunately, the independent roles of hyperinsulinemia and hyperglycemia are difficult to probe in human subjects in vivo , because hyperinsulinemia typically occurs in the setting of hyperglycemia in insulin-resistant and diabetic individuals. Several studies have raised the possibility of a detrimental effect of exogenous insulin therapy on colon cancer risk in type 2 diabetes patients (Chung et al, 2008; Rosato et al, 2016; Yang et al, 2004; Yin et al, 2014). However, such retrospective pharmaco-epidemiologic data are controversial because of the difficulty in defining an appropriate control group, as doing so would require withholding insulin from patients for whom it is medically indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the independent roles of hyperinsulinemia and hyperglycemia are difficult to probe in human subjects in vivo , because hyperinsulinemia typically occurs in the setting of hyperglycemia in insulin-resistant and diabetic individuals. Several studies have raised the possibility of a detrimental effect of exogenous insulin therapy on colon cancer risk in type 2 diabetes patients (Chung et al, 2008; Rosato et al, 2016; Yang et al, 2004; Yin et al, 2014). However, such retrospective pharmaco-epidemiologic data are controversial because of the difficulty in defining an appropriate control group, as doing so would require withholding insulin from patients for whom it is medically indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Among the mechanisms advocated to explain this association, hyperinsulinemia may play a pivotal role, acting as a potent cell mitogen capable of promoting colon cancer growth[8], an hypothesis that is corroborated by indirect findings of a harmful effect of insulin use for CRC risk[9,10]. Other proposed explanations for the increased risk include obesity-related insulin resistance (IR)[11] and cytokine production[12], which may directly influence CRC growth not only through promotion of angiogenesis[13,14], but also by inducing host inflammatory response[13,15] or decreasing natural killer (NK) lymphocyte cytotoxic activity and, thus, the immunological defense against cancer[16].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Many previous studies have suggested the association between type 2 diabetes and the prevalence of various cancers, including colon, liver, breast, pancreas, and endometrial cancers. (3)(4)(5)(6)(7) Although insulin or insulin-like growth factor-1 has been associated with increased colon cancer risk in diabetic patients, (8,9) further studies are required to elucidate the mechanisms by which a diabetic condition increases the occurrence of colon cancer.…”
mentioning
confidence: 99%